The top-down regulation from the prefrontal cortex to insula via hypnotic aversion suggestions reduces smoking craving - Li, Xiaoming; Vollstädt-Klein, Sabine (Human brain mapping, 2019)
Hypnosis has been shown to have treatment effects on nicotine addiction. However, the neural basis of these effects is poorly understood. This preliminary study investigated the neural mechanisms of hypnosis-based treatment on cigarette smoking, specifically, whether the hypnosis involves a top-down or bottom-up mechanism. Two groups of 45 smokers underwent a smoking aversion suggestion and viewed smoking-related pictures and neutral pictures. One group underwent functional magnetic resonance imaging scanning twice (control and hypnotic states), whereas the other group underwent two electroencephalograph sessions. Our study found that self-reported smoking craving decreased in both groups following hypnosis. Smoking cue-elicited activations in the right dorsal lateral prefrontal cortex (rDLPFC) and left insula (lI) and the functional connectivity between the rDLPFC and lI were increased in the hypnotic state compared with the control state. The delta band source waveforms indicated the activation from 390 to 862 ms at the rDLPFC and from 490 to 900 ms at the lI was significantly different between the smoking and neutral conditions in the hypnotic state, suggesting the activation in the rDLPFC preceded that in the lI. These results suggest that the decreased smoking craving via hypnotic aversion suggestions may arise from the top-down regulation of the rDLPFC to the lI. Our findings provide novel neurobiological evidence for understanding the therapeutic effects of hypnosis on nicotine addiction, and the prefrontal-insula circuit may serve as an imaging biomarker to monitor the treatment efficacy noninvasively.
Gesehen am 10.04.2019
First published: 22 November 2018